Transmission Characteristics of Barley Yellow Striate Mosaic Virus in Its Planthopper Vector Laodelphax striatellus - Cao, Qing; Xu, Wen-Ya; Gao, Qiang; Jiang, Zhi-Hao; Liu, Song-Yu; Fang, Xiao-Dong; Gao, Dong-Min; Wang, Ying; Wang, Xian-Bing (Frontiers in Microbiology, 2018)
The most economically important plant viruses are specifically transmitted by phytophagous insects that significantly affect viral epidemiology. Barley yellow striate mosaic virus (BYSMV), a member of the genus Cytorhabdovirus, is transmitted by the small brown planthopper (SBPH, Laodelphax striatellus) in a persistent-propagative manner. However, the infection route of BYSMV in SBPHs is poorly understood. In this study, immunofluorescence confocal laser scanning microscopy (iCLSM) was performed to investigate the route of BYSMV in SBPHs. We unexpectedly found that BYSMV initially infected the hindgut epithelium of SBPHs, instead of the midgut epithelium initially infected by other persistent-propagative viruses. Subsequently, BYSMV disseminated to the hindgut visceral muscles and spread to other parts of alimentary canals, hemolymph, and salivary glands. Comparative analysis of gene expression on viral mRNAs and the BYSMV nucleoprotein by using different molecular detection and immunohistochemistry further demonstrated that BYSMV initially infected and replicated in the hindgut epithelial cells of SBPHs. Collectively, our study provides the first insight into that hindgut is initial infection site of BYSMV that represents a new dissemination route of persistent-propagative viruses.